2022
DOI: 10.3390/diagnostics12071694
|View full text |Cite
|
Sign up to set email alerts
|

Radiomics Diagnostic Tool Based on Deep Learning for Colposcopy Image Classification

Abstract: Background: Colposcopy imaging is widely used to diagnose, treat and follow-up on premalignant and malignant lesions in the vulva, vagina, and cervix. Thus, deep learning algorithms are being used widely in cervical cancer diagnosis tools. In this study, we developed and preliminarily validated a model based on the Unet network plus SVM to classify cervical lesions on colposcopy images. Methodology: Two sets of images were used: the Intel & Mobile ODT Cervical Cancer Screening public dataset, and a private… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Gaona, YJ et al (2022) 7 showed that synthetic images improve the colposcopy diagnosis performance of our AI tool for the classification of cervix images. We propose a combined Deep Learning method (Unet) plus Machine Learning (SVM) to obtain the best index of identification, classification, and prediction of cervix abnormalities through the processing of images.…”
Section: Resultsmentioning
confidence: 94%
“…Gaona, YJ et al (2022) 7 showed that synthetic images improve the colposcopy diagnosis performance of our AI tool for the classification of cervix images. We propose a combined Deep Learning method (Unet) plus Machine Learning (SVM) to obtain the best index of identification, classification, and prediction of cervix abnormalities through the processing of images.…”
Section: Resultsmentioning
confidence: 94%
“…Contrary to most previous studies that conducted preprocessing on colposcopic images [44]- [46], this study advocates for end-to-end segmentation of the region of interest on unaltered colposcopic images, enabling clinicians to make diagnoses based on authentic image data. Given the often blurred borders and complex gradients in raw colposcopic images, high-resolution information is essential for segmenting lesion contours and refining edge details.…”
Section: Introductionmentioning
confidence: 90%
“…Subsequent research has extensively explored various models for medical image segmentation based on U-net. For example, Bai et al [44] segmented colposcopic images using the U-Net model by replacing the fully connected layer with a convolutional layer and employing a deconvolution structure for data upsampling; Zhang et al [45] substituted the convolutional layer in U-Net with a pooling layer and added a dropout layer for colposcopic image segmentation; Yuliana et al [46] employed U-Net to segment ROI in colposcopic images. Additionally, Liu et al [8] compared U-Net, FCN, and SEGNet [47] in CIN image segmentation tasks, finding that U-Net delivers precise edge segmentation.…”
Section: Introductionmentioning
confidence: 99%